Judy Moody Saves the World! [Dada Nálada zachraňuje svet! anglicky] / Book 3. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
It all starts with the Crazy Strip contest and the dream that she, Judy Moody, might one day see her very own adhesive-bandage design covering the scraped knees of thousands. But when her "Heal the World" motif merits only an honorable mention, Judy realizes it's time to set her sights on something bigger. Class 3T is studying the environment, and Judy is amazed to learn about the destruction of the rain forest, the endangered species (not) in her own backyard, and her own family's crummy recycling habits. Now she's in a mood to whip the planet into shape or her name isn't Judy Monarch Moody!